Role of Dynein in Viral Pathogenesis - Mouland, Andrew J. (Dyneins, 2012)
This chapter describes the state of the art machineries that viruses use from viral infection (entry) to the end stage, when new, progeny virus particles disseminate from cells. The development of drugs that target dynein activities during viral replication rely on the disruption of characterized and specific interactions between viral proteins and dynein. Because viruses are parasitic in nature, great reason exists to fully understand the molecular mechanisms underlying host cell protein function and viruses’ dependence on these for additional rounds of infection. Some viral infections induce the assembly of stress granules, including reovirus and respiratory syncytial virus, but others block their assembly during infection. Considering this dependence on dynein activity for assembly, it is possible that viruses co-opt factors of the dynein motor complex during infection, but as a consequence either induce or silence stress granule assembly. This is an emerging field of endeavor, but stress granules and other silencing ribonucleoprotein bodies may represent “dangerous” areas and structures of the cell that viral replication complexes, proteins, and RNAs/DNAs would need to avoid guaranteeing expression and survival. There is research support for the presence of both dynein and kinesin motors driving viral components toward assembly sites. Several viruses, including poxviruses and the vaccinia virus, replicate in cytoplasmic virus factories. Paradoxically, regulatory genes of various viruses enhance and disrupt microtubule integrity and polarization, but this may directly relate to the timing of the replication cycle. This is an area yet to be explored.